2015
DOI: 10.1080/09205063.2015.1034598
|View full text |Cite
|
Sign up to set email alerts
|

High strain-rate response of injectable PAA hydrogel

Abstract: Hydrogel materials have been widely considered as potential soft tissue replacements because of their high permeability, hydrophilicity, and biocompatibility, as well as their low coefficient of friction. Injectable (thermo-responsive) hydrogels can provide support and cushioning at irregularly shaped disease sites, and are thus suitable for use in treating osteoarthritis or degenerative disc disease. However, while some injectable hydrogels have been proven to sustain human body weight during daily activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In our research, we used alginates, which constitute linear polymers composed of (1→4)-α-L-guluronic acid blocks (GG), (1→4)-β-D-mannuronic acid blocks (MM) and, additionally, heteropolymeric sequences of M and G (MG blocks) [11,12]. Moreover, in the case of the preparation of hydrogel or composite materials, alginates are used together with some additional polymers, such as: poly acrylamide (PAAm) [13], poly(acrylic acid) (PAA) [14], gelatin [15], and chitosan [16], as well as PVA [17]. Poly(vinyl alcohol) is very important and interesting, because it characterized by biocompatibility, biodegradability and non-toxicity due to it is commonly used in the medical and pharmaceutical, such as: artificial organs, drug delivery as well as wound dressings.…”
Section: Introductionmentioning
confidence: 99%
“…In our research, we used alginates, which constitute linear polymers composed of (1→4)-α-L-guluronic acid blocks (GG), (1→4)-β-D-mannuronic acid blocks (MM) and, additionally, heteropolymeric sequences of M and G (MG blocks) [11,12]. Moreover, in the case of the preparation of hydrogel or composite materials, alginates are used together with some additional polymers, such as: poly acrylamide (PAAm) [13], poly(acrylic acid) (PAA) [14], gelatin [15], and chitosan [16], as well as PVA [17]. Poly(vinyl alcohol) is very important and interesting, because it characterized by biocompatibility, biodegradability and non-toxicity due to it is commonly used in the medical and pharmaceutical, such as: artificial organs, drug delivery as well as wound dressings.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PAA has been widely used in tissue engineering owing to its small antigenic reaction in vivo. 30,31 Nevertheless, the studies focus primarily on the mechanical properties of bone cement since the inadequate mechanical properties of PAA should not be ignored. These are caused by the increased hydrophilicity as compared to neutral materials and the plasticizing of the solid-phase results by the interstitial fluid in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…As a superabsorbent polyelectrolyte, poly­(acrylic acid) (PAA) is comprised of abundant intramolecular hydrophilic groups. In addition, PAA has been widely used in tissue engineering owing to its small antigenic reaction in vivo. , Nevertheless, the studies focus primarily on the mechanical properties of bone cement since the inadequate mechanical properties of PAA should not be ignored. These are caused by the increased hydrophilicity as compared to neutral materials and the plasticizing of the solid-phase results by the interstitial fluid in vivo. , With respect to the clinical application, changing the expansion performance of the bone cement necessitates intense focus.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that, both LL and NPA were released quickly at first, after the burst period, the release rate slowed down and gradually reached the equilibrium. [29][30][31] Moreover, about 20 % of the LL and NPA were released within the first 2.5 h, and 80 % drugs were released at around 20 h, which were all behaved fast release performance. This indicated that LL and NPA not only were entrapped on the surface, but also distributed in the inner tunnels of the hydrogels.…”
Section: In Vitro Drug Releasementioning
confidence: 91%